Barriers and facilitators to state public health agency climate and health action: a qualitative assessment - Hartwell, Cat; Lovell, Sam; Hess, Jeremy J.; Dolan, Kathleen; Vickery, Jamie; Errett, Nicole A. (BMC public health, 2023)
As the health implications of climate change become more apparent, agencies and institutions across the United States are developing recommendations for state and territorial health agencies (S/THAs) to implement evidence-informed climate and health adaptation strategies. The CDC established the Building Resilience Against Climate Effects (BRACE) framework in 2010 to encourage local and state public health engagement in climate change adaptation. However, even after a decade of the BRACE initiative, the elements that affect the adoption and implementation of climate and health programming by S/THAs are not well understood. Using an implementation science framework, this study sought to further understand and define the barriers and facilitators that determine the breadth and success of climate change and health activities undertaken by state health agencies (SHAs). We conducted focus groups with representatives from SHAs with and without climate and health programs, and analyzed data using the framework method for qualitative research. This study identified funding, state and agency-level prioritization, staff capability and capacity, and political will and polarization as factors that influence the readiness for implementation and implementation climate for climate and health activities. As the impacts of climate change intensify, S/THAs will need to expand resources and capacity, and seek advocacy and assistance from external organizations in order to support the level of engagement required to strengthen climate resilience. Findings from this study have implications for public health policy and highlight potential pathways to expand support for climate and health activities in S/THAs in the U.S.